The Simultaneity of Past and Present in Ian Douglas Smith's The Great Betrayal: The Memoirs of Ian Douglas Smith (1997) - Tagwirei, Cuthbeth (Taylor & Francis (Routledge), 2016)
This article proposes a reading of white Zimbabwean narratives that takes cognisance of how the Rhodesian past and the Zimbabwean present inhabit shared time and place. This reading suggests that white Zimbabwean narratives are characterised by simultaneity. In these texts it can be seen that the (Rhodesian) past and the (Zimbabwean) present appear incommensurate but nevertheless coeval. Using Ian Smith’s The Great Betrayal: The Memoirs of Ian Douglas Smith (hereafter referred to as The Great Betrayal), I argue that in Zimbabwe, like in other former colonies, the colonial past exists alongside the post-colonial present despite persistent calls by the new post-colonial governments for former colonisers to forget. In Smith’s The Great Betrayal, the past inhabits the present in three forms: as an endurance of the founding principles of British Empire; as an indictment of the Zimbabwean present; and as a strategic emplacement of white Rhodesians within a new Zimbabwe.